La interpretación como vía didáctica hacia la comprensión del derecho:análisis y propuesta a partir deltexto literario La Verdadde Luigi Pirandello - Astwood, Ivan (2023)
The purpose of this article is to show, through examples taken fromtheoretical and literary texts, how interpretation can constitute a didacticway or path to develop a broader understanding of law based on lite-rature. In order to illustrate this purpose, a short story by Luigi PirandelloentitledThe Truthwill be analyzed from the point of view of the ideaof interpretation put forward by Ronald Dworkin in the articleHow arelaw and literature alike?, and then a text by Alf Ross (Tû-Tû) will be usedto show how this interpretation can serve as a didactic path toward sunderstanding law. Finally, there is an appendix containing examplesof hypothetical didactic activities aimed at developing understanding ofa legal topic proposed in one of the studied texts